KOMPLIKASI HIPERTENSI DALAM KAITANNYA DENGAN PENGETAHUAN PASIEN TERHADAP HIPERTENSI DAN UPAYA PENCEGAHANNYA - Zaim Anshari (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2020)
Hypertension is a disease caused by the high blood pressure of a person, both in terms of systolic and diastolic. Hypertension is one of the uncontagious diseases that can kill someone secretly. Therefore, the researchers need to know the level of knowledge of hypertension patients to hypertension and prevention efforts. The study took a description technique to know the patient's knowledge of his illness and prevention efforts to prevent complications. The samples used were as many as 42 people selected with the purposive technique. The results show that while existing hypertension patients have a low level of education and are between 46-65 years of age, the knowledge of hypertension and its prevention to reduce the risk of complications belongs to a suitable category so that they are more alert about hypertension.